Tingkat Pengetahuan Ibu Menyusui tentang Pentingnya Pemberian Kolostrum pada Bayi Baru Lahir di Klinik Pratama Murni Tahun 2025 - Friska Apriani Sihombing; Rayani Simanullang (Lembaga Pendidikan dan Penelitian Manggala Institute, 2026)
Colostrum is the first fluid secreted by the mammary glands. The highest content in colostrum is antibodies that are ready to protect the baby. The protein content in colostrum is higher compared to the protein content in mature milk. The contents include 8.5% protein, 2.5% fat, 3.5% carbohydrates, 0.4% salt and minerals, 85.1% water, antibodies and higher immunoglobulin content when compared to mature breast milk. The purpose of this study was to determine the Relationship of the Level of Knowledge of Breastfeeding Mothers About the Importance of Providing Colostrum to Newborns at the Pratama Murni Clinic in 2025. The sample and population that will be used in this study are all 35 postpartum mothers. The results of bivariate data analysis using the Chi Square test and logistic regression to analyze the most dominant factors. Based on the results of the chi-square test, it is known that the p value = 0.019 < 0.05 means that there is a significant influence between knowledge on giving Colostrum. The results of the multiple logistic regression test show that the most dominant factor is the knowledge of breastfeeding mothers at the pure primary clinic in 2025. Knowledge is closely related to education, where it is expected that with higher education, the person will have broader knowledge, including in giving colostrum breast milk to newborns.